Analisis Korelasi antara Kemampuan Pemecahan Masalah dan Miskonsepsi pada Materi Fluida Statis - Aurriel Magita Arsha Dittya; Nur Endah Susilowati; Duden Saepuzaman; Erni Ernawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Misconceptions in physics learning can hinder students conceptual understanding and affect their ability to solve problems effectively. Therefore, investigating the relationship between misconceptions and problem-solving ability is important to provide information for improving physics learning, particularly in static fluid concepts. This study aims to analyze the correlation between students’ problem-solving ability and misconceptions in static fluid material. The study employed a quantitative correlational design involving 31 students of class XI MIPA at a senior high school in Bandung. The sampling technique used was total sampling. Data were collected using a misconception test consisting of 10 two-tier multiple-choice questions and a problem-solving ability test consisting of 10 essay questions. Data analysis was conducted using the Kolmogorov-Smirnov normality test and Spearman’s rho correlation test. The normality test results indicated that both misconception and problem-solving ability data were not normally distributed (p < 0.05). Therefore, the Spearman correlation test was employed. The results showed a correlation coefficient of 0.291 with a significance value of 0.090 (p > 0.05). These findings indicate that there is a positive but statistically insignificant correlation between misconceptions and problem-solving ability. The correlation level is categorized as weak. Therefore, misconceptions do not significantly affect students’ problem-solving ability in static fluid material.